Cardiac Complications Caused by Respiratory Syncytial Virus Infection: Questionnaire Survey and a Literature Review - Hisashi Kawashima MD, PhD; Natsuko Inagaki MD, PhD; Toshihiro Nakayama MD; Shinichiro Morichi MD, PhD; Shigeo Nishimata MD, PhD; Gaku Yamanaka MD, PhD; Yasuyo Kashiwagi MD, PhD (SAGE Publishing, 2021)
We investigated 22 cases of patients with myocarditis during respiratory syncytial virus (RSV) infection by a questionnaire survey, and performed a literature search to clarify their characteristics. The age distribution was divided into 2 groups, that is, 1 group comprised of patients younger than 4-years old and the other comprised patients older than 15 years. ECG demonstrated disturbance of the conduction system (AV block) in 7 out of 18 patients (38.8%), myocardial damage (ST-T change) in 9 out of 18 patients (50.0%), and tachycardia in 3 out of 18 patients (16.6%). Echocardiography displayed a robust decrease in left-heart function in 12 out of 14 patients. The outcome was 2 deaths, 1 pacemaker placement, 4 patients with mild sequel. Our data suggest that RSV myocarditis caused by RSV infection can be divided into 3 different pathophysiologies, characterized by disturbance of the conduction system, myocardial damage, and increase of autonomy.